COVID-19 and Kingdom of Saudi Arabia - Saleh A Eifan; Atif Hanif (Journal of Clinical Microbiology and Biochemical Technology - Peertechz Publications, 2020)
The novel coronavirus disease originated from the Hubei Province of China in December 2019 [1]. The spread of infection is continuous across the world. Previously different human corona viruses like HCoV-229E, HCoV-OC43, HCoV-NL63 and HCoVHKU1 of animal origin (BAT) were known to cause respiratory illnesses in humans.